The Haghighi house , Iran - Abdul Rahim, Asiah (s.n, 2012)
Islam has given us a general framework within which we may operate and create a built environment that suite the requirements of age, circumstances, climate, geography and culture. Practically, the Islamic architecture principles represent the religion of Islam that has been translated into reality at the hands of Muslim as it is also a representation of Islamic culture and civilization. The application of veil architecture in the Iranian traditional courtyard reflect the social, culture and economy of the owner, it is also a mean and adaptation of architectural design elements that is in compliance with the Islamic belief and teaching